Analisis Dampak Penggunaan Gadget Sebelum Tidur terhadap Kualitas Tidur dan Prestasi Belajar Siswa - Ridha Sakina Oktari; Sartono Sartono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Advances in technology have led to an increase in gadget use among students, including the activity of using electronic devices before bedtime. This study used a qualitative approach, collecting data through student questionnaires and in-depth interviews with classroom teachers. The study involved 10 Year 5 students as main respondents and 1 class teacher as a supporting respondent. The results identified four themes: (1) students' habits in using gadgets before bedtime, (2) students' views on the impact on sleep quality, (3) teachers' views on the impact on students' learning, and (4) parents' role in supervision. The results showed that the majority of 5th grade students use gadgets 30-120 minutes before bedtime, with the habit of using gadgets to play games, watch videos and use social media. This study also found that students with good parental regulation and supervision of gadget use had better sleep quality and more stable academic performance. The results of this study highlight the importance of education on the wise use of gadgets, as well as the active role of parents and schools in regulating and supervising students' digital activities, especially before bedtime, to support optimal academic development.